2019
DOI: 10.1002/jum.15162
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ultrasound and Shear Wave Elastography for the Diagnosis of Breast Cancer–Related Lymphedema

Abstract: Objectives To assess the feasibility of ultrasound and shear wave elastography (SWE) in the diagnosis of breast cancer–related lymphedema. Methods Forty‐one patients with a history of unilateral breast surgery and axillary dissection or sentinel lymph node excision were included in this prospective study. The patients were classified as having normal findings, latent lymphedema, and clinical lymphedema on the basis of a physical examination, lymphedema index scores, and limb circumference measurements. The thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
(71 reference statements)
0
14
0
2
Order By: Relevance
“…It can measure and reflect the tissue elasticity value, quantitatively assess the hardness of lesions, and provide objective data for diagnosis. In the report (12), SWE has been prospectively confirmed that it could reflect lymphedema even at a latent stage for patients with breast cancer after surgery because of the fibrotic soft tissue change in stiffness. Our study aimed to explore the application of SWE's advantage in measuring tissue hardness combined with SWE in the differential diagnosis of TNBC and non-TNBC, thus enhancing the imaging foundation for preoperative diagnosis of TNBC.…”
Section: Introductionmentioning
confidence: 83%
“…It can measure and reflect the tissue elasticity value, quantitatively assess the hardness of lesions, and provide objective data for diagnosis. In the report (12), SWE has been prospectively confirmed that it could reflect lymphedema even at a latent stage for patients with breast cancer after surgery because of the fibrotic soft tissue change in stiffness. Our study aimed to explore the application of SWE's advantage in measuring tissue hardness combined with SWE in the differential diagnosis of TNBC and non-TNBC, thus enhancing the imaging foundation for preoperative diagnosis of TNBC.…”
Section: Introductionmentioning
confidence: 83%
“…These results could serve future developments of in vivo diagnostic and surgery assistance devices dedicated to the pituitary gland, for instance the invasive needle elastography technique [ 16 ] or the development of noninvasive shear wave elastography probes. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…e ultrasonic radiation force comes from the change of linear momentum when the ultrasonic wave propagates in the medium, i.e., the ultrasonic wave in the medium will produce energy density difference because of absorption or scattering. Only in a viscoelastic liquid or solid with a certain attenuation coefficient can the sound radiation force be produced [12]. e action of acoustic radiation force by the emission of a series of detection pulses can get the corresponding position of the tissue vibration.…”
Section: Shear Wave Elastography-assisted Ultrasound Breastmentioning
confidence: 99%